2017
DOI: 10.22159/ajpcr.2017.v10i9.19076
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Laughter Therapy on Blood Pressure Among Patients With Hypertension

Abstract: Objective: Hypertension is a major non-communicable disease prevailing globally. This study was conducted to determine the effectiveness of laughter therapy on blood pressure among patients with hypertension at a selected hospital, in Kancheepuram District. Methods:A quantitative approach of pre-experimental one group pre-and post-test design was chosen for this study. A total of 50 samples were included in the study using purposive sampling technique. Pre-test was done using the structured instrument, and lau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, a cross-sectional study performed in Jammu has concluded that most of the hypertensive patients (72.5%) were concerned about the symptoms [6], alternatively, another study conducted in Kerala has suggested that the majority of hypertensive patients lack the knowledge on stroke prevention [7]. Although cardiac walking and laughter therapy has recently been found as maintaining optimum blood pressure in HTN patients [8,9], one of the major successes in medicine in the past decades was the treatment of HTN. The striking therapeutic advancement provided a greater capability of controlling blood pressure in hypertensive patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, a cross-sectional study performed in Jammu has concluded that most of the hypertensive patients (72.5%) were concerned about the symptoms [6], alternatively, another study conducted in Kerala has suggested that the majority of hypertensive patients lack the knowledge on stroke prevention [7]. Although cardiac walking and laughter therapy has recently been found as maintaining optimum blood pressure in HTN patients [8,9], one of the major successes in medicine in the past decades was the treatment of HTN. The striking therapeutic advancement provided a greater capability of controlling blood pressure in hypertensive patients [10].…”
Section: Introductionmentioning
confidence: 99%